The Impact of Bokashi and NPK Fertilizer Applications on Pakchoy (Brassica rapa L.) Growth - Ahmad Raksun; Lalu Zulkifli; I Wayan Mertha; Didik Santoso; Moh. Liwa Ilhamdi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The growth of pakchoy is determined by the availability of nutrients around its root system. Research on the effect of bokashi and NPK fertilizer on pakchoy vegetative growth was conducted from May to August 2025. This study aimed to measure the increase in pakchoy growth after being given bokashi and NPK fertilizer. The pakchoy planting experiment was conducted using a completely randomized design with two factors. Pakcoy was planted in experimental pots, given bokashi treatment 3 days before planting and given NPK fertilizer 15 and 22 days after planting. The results of the experiment showed that: (1) the vegetative growth parameters of pakchoy given 1.5 g of NPK fertilizer were significantly different from the control, except for leaf width, (2) the vegetative growth parameters of pakchoy given 1.6 kg of bokashi were significantly different from the control, except for leaf width, (3) The interaction of bokashi and NPK fertilizer did not significantly affect the vegetative growth of pakchoy.